IMPROVING THE EFFICIENCY OF FUNCTIONING OF MACHINERY AND APPARATUS EQUIPMENT BY MANAGING THE RELIABILITY OF THEIR SYSTEMS - PATRASHKU, OLGA; BRATSLAVETS, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2023)
Increasing and maintaining the reliability of technical means used in agricultural production is largely determined by the strategy for the maintenance and repair of machinery and equipment. At present, a sufficient number of strategies have been developed to effectively perform technological operations of technical service and thereby ensure the necessary reliability of technical means. Any maintenance strategy for the repair of machinery and equipment is designed to keep products in working condition and in proper appearance; reducing the intensity of wear of parts; prevention of failures and malfunctions, as well as their identification in order to eliminate them in a timely manner. Each of the strategies, being a preventive measure, is a set of organizational and technical measures of a protective nature aimed at ensuring the constant technical readiness of machines and mechanisms for operation and preventing increased wear of their parts, and has its own characteristics. An analysis of the features of domestic and foreign strategies for the maintenance of machinery and equipment made it possible to determine their advantages and disadvantages of mobile agricultural equipment. Based on the assessment of the strategies, measures are proposed to improve the system of maintenance and repair of agricultural machines, which make it possible to increase the efficiency of the use of machines and equipment by reducing the recovery time of the product and increasing its interval reliability. The essence lies in the operational management of the reliability of the main units and systems of the technical facility, which, using the methods of periodic monitoring of the parameters and modes of operation of the product, makes it possible to determine the need for routine maintenance, their labor intensity and efficiency. The proposed method of operational control of product reliability provides an opportunity to develop measures to improve the organization of maintenance and repair; determine the optimal technology for routine maintenance; choose a rational centralization of maintenance points and justify the expediency of having technical service units.
Keywords: maintenance; technical facility; operational management; parameters and modes of operation; product; routine maintenance; technical service